Systemic effects of international educational and scientific links. Proposals for the development of educational and scientific national system in Georgia. (2016) - Gagnidze, Ineza; Maisuradze, Nana
The present paper describes the international educational and scientific links of Georgia. These links promote the development of long-term and close relationship between countries. After the collapse of the Soviet system, Georgia became a transition economy country and the country gained the possibility to widen its educational and scientific links. Reforms are carried out in different directions, including the system of science and education. However, scientific study of the current reforms is presented only as separate evaluations, which, from our point of view, is not sufficient for achieving long-term effective results. By presenting educational and scientific links in the paper jointly, we have developed a model, which shows possible systemic synergistic effects of these links. Such systemic approach is directly connected to the innovative development of the country.